The perception of Malaysian palm plantation companies towards the adoption of a proposed standard of agriculture (IAS 41) in Malaysia - Nur Naimah Mohamed (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2015)
The International Accounting Standard of Agriculture (IAS 41) standard has raised many controversial issues particularly relating to agriculture activities where the income-producing biological assets have long economic lives that stretch beyond ordinary accounting periods. Such biological assets include palm trees, rubber trees, timbers etc. Based on the situation in Malaysia, the standard still needs revision so that it may be extended to include palm trees that are long-lived biological assets. Thus, the main objective of this study is to examine the current accounting method as practised by Malaysian palm plantation companies in relation to palm oil trees, which fall under biological assets. The secondary objective is to examine the Malaysian palm plantation companies' perception towards potential challenges if the IAS 41 is adopted in Malaysia. This study used the multiple case study research approach to note the differences in opinion or perceptions between small and big palm plantation companies. In order to do this, six palm plantation companies were selected and 13 employees from these companies were interviewed. The findings showed most of the palm plantation companies gave negative perspectives regarding the application of the proposed standard. This is due to the complexity of IAS 41; and the absence of fair value market especially for palm oil trees and other long-lived biological asset. However, most of palm plantation companies agreed that this standard is appropriate for short-lived biological assets. Overall, it is hoped that the standard setters will revise the existing agricultural standard and find some practical solutions to the problem of the inactive market in order to ensure that the IAS 41 will be relevant and applicable to all biological assets.